Effect of a Modified Irrigation Protocol on the Cleanliness of Moderately Curved Canals - Voegeli, Garance; Bella, Enrico Di; Mekki, Mustapha; Machtou, Pierre; Bouillaguet, Serge (European Journal of Dentistry, 2020)
Objectives This study tested the hypothesis that modifying the sequence of sodium hypochlorite (NaOCl)/ethylene diamine tetra-acetic acid (EDTA) irrigation during root canal shaping would improve apical cleanliness in moderately curved canals.Materials and Methods Forty-five root canals were prepared using Protaper Gold with three irrigation protocols. Standard irrigation (SI) used 0.5 mL 3% NaOCl between each instrument, followed by 5 mL 17% EDTA manually agitated for 30 seconds. Reverse irrigation (RI) used 0.5 mL of 17% EDTA between each instrument, then 5 mL of 3% NaOCl, manually agitated for 30 seconds. Reverse irrigation plus (RI+) was similar to RI, except NaOCl (5 mL), used as a final rinse, was allowed to interact for 3 minutes with dentin before manual agitation (30 seconds).Root canal cleanliness was evaluated under the scanning electron microscope (SEM) (Hulsmann score); the chemical composition of dentin after irrigation was analyzed by energy dispersive X-ray (EDX).Statistical Analysis Results were compared using Kruskal–Wallis ANOVA by ranks and Wilcoxon matched paired posthoc tests. A Chi-square test assessed whether the best cleanliness would demonstrate a significant association with one irrigation protocol; odds ratio calculation was performed using score “1” versus score “2 or more” (2+) (p < 0.05).Results In the apical region, cleanliness was better in RI+ than SI and both significantly better than RI. Odd ratios indicate that the cleanliness in RI+ was significantly better than RI and SI groups (p < 0.000 and 0.003, respectively). Independently of the irrigation protocol, EDX analyses showed no chemical alteration of root dentin.Conclusions Using 17% EDTA during shaping, followed by 3% NaOCl rinse for 3 minutes, improved apical cleanliness without inducing erosion of dentin.
Keywords: EDTA; endodontic; irrigation; NaOCl; smear layer